2013
DOI: 10.1210/en.2012-2136
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen, Predominantly via Estrogen Receptor α, Attenuates Postpartum-Induced Anxiety- and Depression-Like Behaviors in Female Rats

Abstract: Contributions from estrogen receptor (ER) subtypes (ERα and ERβ) to postpartum anxiogenic and depressive responses remain unresolved in rats. Using the elevated-plus maze (EPM) and forced swim (FS) tests, we confirmed that primiparous rats exhibited anxiogenic and depressive responses 3 weeks postpartum, improved 5 weeks postpartum (EPM), and recovered at 5 (FS) or 10 weeks postpartum (EPM) compared with diestrus nulliparous females. Immunohistochemistry suggested that these behavioral changes were temporally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(40 citation statements)
references
References 61 publications
2
36
1
Order By: Relevance
“…We have observed depressive-like behaviors in primiparous female rats at 3 weeks postpartum compared with nulliparous rats (53). Furthermore, decreased expression of ERα (not ERβ), and increased expression of BDNF and its receptor TrkB in the medial amygdala were observed at 3 weeks postpartum (53).…”
Section: Estrogen and Postpartum Depressionmentioning
confidence: 90%
“…We have observed depressive-like behaviors in primiparous female rats at 3 weeks postpartum compared with nulliparous rats (53). Furthermore, decreased expression of ERα (not ERβ), and increased expression of BDNF and its receptor TrkB in the medial amygdala were observed at 3 weeks postpartum (53).…”
Section: Estrogen and Postpartum Depressionmentioning
confidence: 90%
“…However, ER subtypes mediated by anxiolytic actions are not fully accepted. For example, estrogen reduces postpartum-induced anxiety-and depression-like behavior predominantly via ER␣ (Furuta et al, 2013). The behavioral changes are temporally associated with decreased ER␣ but not with ER␤ expression in the medial amygdala (Furuta et al, 2013).…”
Section: Anxiety Estrogen and Amygdalamentioning
confidence: 99%
“…For example, estrogen reduces postpartum-induced anxiety-and depression-like behavior predominantly via ER␣ (Furuta et al, 2013). The behavioral changes are temporally associated with decreased ER␣ but not with ER␤ expression in the medial amygdala (Furuta et al, 2013). Studies using a combination of pharmacological and genetic approaches have demonstrated that the anxiolytic actions of estradiol are mediated by ER␤ in female mice (Lund et al, 2005;Oyola et al, 2012).…”
Section: Anxiety Estrogen and Amygdalamentioning
confidence: 99%
“…Of note, this regulation of hippocampal spine density is dependent on glutamate receptor (NMDA) signaling (358), which has also been implicated in the etiopathogenesis of depression (162,183). In the amygdala, estradiol also increases BDNF, TrkB, and proline-rich receptor-like protein kinase 2 (pERK2), which is associated with decreased depressive-like behavior (101).…”
Section: Effects Of Reproductive Steroids On Biological Systems Implimentioning
confidence: 99%